The Validity of Android-Based Biology Teaching Materials to Improve Students’ Concept Mastery - Rusdiana Putri, Kurnia Dewi; Muhlis, Muhlis; Ramdani, Agus (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
This study aims to develop appropriate android-based teaching materials to improve students’ mastery of concepts. This study is a qualitative descriptive study to assess and obtain the quality of a valid android-based learning material knowledge instrument to improve students’ conceptual mastery skills. In addition to developing android-based biology teaching materials, researchers also develop a syllabus, lesson plans (RPP), and students’ concept mastery instruments. Data collection techniques use validation sheets by three expert lecturers who are competent in their field. The data analysis technique uses the Aiken’V index. The results of the feasibility test show that: 1) android-based biology teaching materials (0.83); 2) Syllabus (0.82); 3) RPP (0.82); and 4) concept mastery instruments (0.78) categorized as very valid and valid criteria. In conclusion, this android-based biology teaching material is feasible to be applied and implemented in learning.